Active thermography as a tool for internal composite structure observation and evaluation. Issue 6 (3rd December 2018) - Majewska, Katarzyna; Mieloszyk, Magdalena; Ostachowicz, Wieslaw
Abstract : Purpose: The purpose of this paper is to study if it is possible applying infrared thermography (both vibro and pulsed) to detect and localise material discontinuities as well as to find the place where the inclusion was introduced. Design/methodology/approach: The experimental investigation is performed on samples manufactured during infusion process. The measurements were performed on three four-layered rectangular composite samples with discontinuities. The discontinuities introduced in the samples were as follow: all three samples between first and second layer counting form the bottom two optical fibres (OFs) were embedded and additionally: sample no. 1 – one of the OF was broken, sample no. 2 – the drop of water was introduced, and sample no. 3 – the little amount of dust was introduced. Findings: For some discontinuities, the vibrothermography is excellent tool (placement of broken OF, drop of water), for same is not sufficient (healthy OFs or dust). For dust, the pulsed thermography seems to be the required tool. Different approaches (vibrothermography and pulsed thermography) for the same sample will confirm that for same defects vibrothermograpy is better and for some pulsed thermography – complex combination of different thermography approaches is needed to have complex response about sample structural condition. Originality/value: The presented paper is an original research work. There are very limited literature papers applying both vibro and pulsed thermography for one problem. The assessment of different discontinuities (inclusions) and detailed analysis is presented.